The Death of the Beluga Sturgeon (Huso huso) Rediscovered in the Küçükçekmece Lagoon: Let’s Focus on Causes - Özcan Gaygusuz; Latife Köker; Gökhan Tunçelli; Devrim Memiş (Aquatic Sciences and Engineering)
Sturgeon, a key species in fisheries and aquaculture due to their high economic and ecological value, face numerous challenges in their natural habitats. The spawning grounds in rivers, essential for sturgeon reproduction, are often compromised by the blockage of migration routes caused by various obstacles. Lagoons, providing favorable conditions for fish growth, are also hunting grounds for predatory fish species. The Küçükçekmece Lagoon, located within İstanbul's borders in Türkiye, stands as one of the most significant lagoons in the region, especially noted for its position on the bird migration route. However, it has been suffering from unplanned urbanization, leading to a notable decline in water quality due to improper urban planning and industrial activities over the years. This decline is aggravated by waste drainage into the lagoon's wetland area. Notably, the last sturgeon sighting in the Küçükçekmece Lagoon was in 1986. After approximately 35 years, the discovery of two deceased beluga sturgeon (Huso huso) in the lagoon, which connects to the Marmara Sea in Türkiye, marked a significant event. This study aims to investigate the causes behind the death of these beluga sturgeons and also proposes potential solutions for enhancing the ecosystem's vitality of the lagoon. These solutions include addressing waste drainage, ensuring shoreline compliance, improving the sediment structure laden with organic matter, and artificially introducing fresh water. Such measures are crucial for the restoration and maintenance of the ecological balance in the Küçükçekmece Lagoon, which is vital for the survival of significant species like the sturgeon.